Sebuah Penelitian Tunggal: Pendekatan Membaca Mundur Pada Kasus Latah Usia 44 Tahun di Jakarta Barat - Agustina; Gilang Ramadhan (Politeknik Arutala Johana Hendarto [d.h. Akademi Terapi Wicara], 2025)
Background: Latah is a linguistic action when someone is surprised and shocked, accidentally uttering words spontaneously and is not aware of what they are saying. Latah symptom are five, Echolalia, Coprolalia, Echopraxia, Automaticobedience, and AutoEcholalia. This deviant behavior can cause someone to be hampered in conveying something to the person he is talking to so that it can cause anxiety, embarrassment or lack of self-confidence, this has a big influence on communication. The prevalence of latah sufferers in Indonesia is dominated by Javanese or those related to Javanese people. Objective: To test whether the Reading Backward method is an effective intervention for patients with latah rhythm disorders. Method: The single subject design ABA type, subject was a 44-year-old woman with latah rhythm disorders. Data collection was conducted through pre-test as baseline (A1), Intervention as baseline (B) ang post-test as baseline (A2). Results: The intervention was conducted during 10 therapy session and consisted of reading bacward indicating improvement. Visual analysis revealed a stable and consistent downtrend in symptom of latah. Conclusion: This emphasizes the importance of appropriate intervention in addressing effective interventions for language rehabilitation in patients with latah rhythm disorders.